A new type of inner-side working head for automatic drilling and riveting system. Issue 1 (4th February 2019) - Jiang, Junxia; Bian, Chen; Bi, Yunbo; Ke, Yinglin
Abstract : Purpose: The purpose of this paper is to design, analyze and optimize a new type of inner-side working head for automatic horizontal dual-machine cooperative drilling and riveting system. The inner-side working head is the key component of automatic drilling and riveting system, and it is a challenge to design an inner-side working head which must be stiffness and stable with a compact structure to realize its functions. Design/methodology/approach: According to the assembly structure features of large aircraft panels and riveting process requirements, a new type of inner-side working head is designed for pressure riveting. The force condition of the inner-side working head during the riveting process is analyzed and the deformation model is established. Design optimization is performed based on genetic algorithm and finite element analysis. The optimized inner-side working head is tested with automatic horizontal dual-machine cooperative drilling and riveting system. Findings: The deformation model provides the precision compensation basis for control system. Application test results show that the automatic drilling and riveting system can realize assembly of large aircraft panel with high efficiency and quality through the inner-side working head. Research limitations/implications: The inner-side working head has been used in aircraft panel assembly. Practical implications: The inner-side working head has been used in aircraft panel assembly. Originality/value: This paper presents the design, analysis and optimization of a new type of inner-side working head which can realize automatic riveting for aircraft panel. The research will promote the automation of aircraft panel assembly.